KOTAK SAMPAH BERBICARA - Selah; Tesah Aldi Parani; Ocsirendi; Yudhi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Most of the activities certainly can not be separated from the garbage. As human activities increase, the amount of waste produced also increases. This can be seen from the amount of garbage scattered around the environment. Trash boxes are often found with manual systems, so people feel lazy to throw garbage because they have to first open the lid of the trash can. From these problems, a final project was made, namely an automatic and talking trash box. The goal is to attract individual interest in disposing of waste in its place. The methods used in the final project are literature study, hardware and software design, hardware and software manufacture, hardware and software testing so that the tool can function properly. The experiment was carried out by taking ultrasonic sensor data 1 (object detection) used to detect the presence of objects in front of the sensor with a distance of 5 - 55 cm with a percentage error. For data collection ultrasonic sensor 2 (capacity detector) by testing various types of waste. For the types of waste, namely cardboard, plastic bottles, books, HVS paper, shoes, bags, tissue, plastic, cell phone cases, and paper bags with percentage capacities of 25%, 50%, and 75%. Testing the servo motor to find out the right angle of rotation on the lid of the trash box and testing the mini dfplayer to find out the sound recordings that are formatted can be in sequence.